Model characteristics of physical development and special physical preparedness of swimmers 12-15 years old - Politko, O. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to develop model characteristics of indicators of physical development and special physical preparedness of young athletes of 12-15 years.